Introduire la dimension historique au collège en France - DANIELLE M. E. FAUQUE (Metaichmio Publications, 2007)
The introduction of historical elements within the secondary education of France actually tends to be generalized nowadays. Several activities that draw upon the history of science are proposed for 11-15 year-old students within the official teacher's guide. The invention of Volta's battery in 1800, which is detailed here, is one of these. This activity is replaced in the context of the contemporary education system of France, as well as during the last thirty years when the introduction of the history of science in our secondary education has been evolving.